Revisiting the SSRI vs. placebo debate in the treatment of social anxiety disorder: the role of expectancy effects, neural responsivity, and monoamine transporters - Furmark, Tomas; Wahlstedt, Kurt; Faria, Vanda (Frontiers in Psychology, 2025)
Selective serotonin reuptake inhibitors (SSRIs), widely used for anxiety and depression, are often criticized for their perceived similarity in efficacy to placebo treatments and the unclear connection between brain serotonin levels, on one hand, and the symptomatology of these disorders, on the other. In this perspective paper we discuss the complex mechanisms behind SSRI and placebo treatments in managing social anxiety disorder (SAD), focusing on both pharmacological and expectancy effects. Through a series of neuroimaging studies using positron emission tomography (PET), we investigated the neural, neurochemical and behavioral changes associated with SSRI and placebo responses in SAD patients. Results from one study revealed that both SSRI and placebo responders showed equal reductions in amygdala activity, a region central to fear processing, as well as comparable improvements in social anxiety symptoms. These findings suggest shared neural pathways between SSRIs and placebos, possibly related to response expectancies. In another study, we manipulated patient expectations using a deception design, showing that overt SSRI treatment yielded greater symptom reduction than covert administration. PET results further underscored the influence of expectation on dopamine signaling. Furthermore, PET data on serotonin transporters indicated that serotonin reuptake inhibition alone does not fully account for SSRIs' clinical efficacy, as serotonin transporter occupancy was not correlated with symptom improvement. In yet another study, combining SSRIs with cognitive-behavioral therapy (CBT) led to more robust and longer-lasting outcomes than placebo combined with CBT, with distinct effects on brain monoamine transporters. Overall, these findings emphasize the intricate interplay between pharmacology, brain mechanisms, and psychological expectations in the treatment of SAD.